Tailoring Authenticity: A Media Post-Mortem of the Daguerreotype through the NFT. - Kilroy, Robert Thomas (19: Interdisciplinary Studies in the Long Nineteenth Century, 2025)
This article attempts to test the ways nineteenth-century spectatorship is viewed and interpreted in contemporary artistic practices by exploring the impact of the early decades of photography in terms of ongoing developments in contemporary visual technology. The central question is: how might a contemporaneous object like the non-fungible token (NFT) allow us to think through a historical object such as the daguerreotype? The first half of the article outlines the conceptual grounds for this analysis from which a new methodology, what I term a media post-mortem and its supporting concept of symptomatic plasticity, is applied and developed. The broader aims of the article are twofold: (1) to propose a new approach to the study of art historical phenomena that is supported and justified by a rigorous and innovative engagement with new conceptual tools; and (2) to map a new direction for the study of media by way of a more intense, diagnostically acute focus on the question of materiality.